Discovery, Synthesis and Characterization of a Highly Muscarinic Acetylcholine Receptor (mAChR)‐Selective M5‐Orthosteric Antagonist, VU0488130 (ML381): A Novel Molecular Probe. Issue 8 (1st April 2014) - Gentry, Patrick R.; Kokubo, Masaya; Bridges, Thomas M.; Cho, Hyekyung P.; Smith, Emery; Chase, Peter; Hodder, Peter S.; Utley, Thomas J.; Rajapakse, Anuruddha; Byers, Frank; Niswender, Colleen M.; Morrison, Ryan D.; et al.
Abstract Of the five G‐protein‐coupled muscarinic acetylcholine receptors (mAChRs; M1–M5), M5 is the least explored and understood due to a lack of mAChR subtype‐selective ligands. We recently performed a high‐throughput functional screen and identified a number of weak antagonist hits that are selective for the M5 receptor. Here, we report an iterative parallel synthesis and detailed molecular pharmacologic profiling effort that led to the discovery of the first highly selective, central nervous system (CNS)‐penetrant M5‐orthosteric antagonist, with sub‐micromolar potency (hM5 IC50=450 nM, hM5Ki=340 nM, M1–M4 IC50 >30 μM), enantiospecific inhibition, and an acceptable drug metabolism and pharmacokinetics (DMPK) profile for in vitro and electrophysiology studies. This compound will be a powerful tool and molecular probe for the further investigation into the role of M5 in addiction and other diseases.